Incidence and impact of activating mutations of the RAS-RAF- MEK-ERK pathway in patients with philadelphia-negative (Ph-negative) myeloproliferative neoplasms (MPNs) and myelodysplastic/myeloproliferative disorders-unclassified (MDS/MPD-U) - Santos, Fabio P. S. (2014)
Hosp Israelita Albert Einstein, Sao Paulo, Brazil